The last age of the church - d; Todd, James Henthorn, 1805-1869 (Salt Lake City, UT : Project Gutenberg, 2023)
"The Last Age of the Church" by John Wycliffe is a theological treatise composed in the mid-14th century. This work reflects the author's inquiries into Christian doctrine and the conditions of the Church at that time. It delves into prophetic interpretations, particularly surrounding the concept of Antichrist, while critiquing the practices within the Church, including issues of clerical corruption and simony. In this treatise, Wycliffe examines the state of the Church and its impending tribulations, linking them to historical prophecies that suggest a time of great spiritual challenge. He presents a chronological view of the Church's age, articulating that the era leading up to the arrival of Antichrist will be marked by the rise of clerical abuses and moral decay. Citing various theological authorities, he discusses how these tribulations have symptoms in the form of spiritual and institutional failings, advocating for reform and a return to genuine Christian values. The piece serves as both a warning and a call to action for the faithful to recognize and address the waning integrity of ecclesiastical authority. (This is an automatically generated summary.)
Release date is 2023-03-10
Brian Wilson, Charlene Taylor and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Church history -- Middle Ages, 600-1500 -- Sources